Investigation of a Mathematical Model and Non-Linear Effects Based on Parallel-Substrates Biochemical Conversion (Contemporary Mathematics, 2024)
According to the broad applicability and advancements made in addressing complex non-linear problems, Researchers have been actively involved in addressing the accurate approaches to solve non-linear problems in fields such as chemical science, material science, and image processing. In this paper, the Amperometric response of catalase-peroxidase (parallel-substrates) conversion has been discussed. The Mathematical model relies on a set of non-linear differential equations that describe the reaction and diffusion of the system. The analytical methods were extended to derive the approximate solution of the non-linear reaction-diffusion equation. The straightforward and concise analytical expressions for the concentrations and current of the Biosensor are developed. This study includes the computational resolution of the problem by utilizing a MATLAB program. A comparison between analytical outcomes and those derived numerically has been conducted. The analytical findings presented are dependable and offer an effective comprehension of the behaviour of this system.
Keywords: mathematical modelling, Akbari-Ganji’s method (AGM), differential transform method (DTM), non-linear differential equations